Evaluation of Health Status and Factors Associated with Health Behaviors among Adults in Saudi Arabia (Asian Journal of Pharmaceutics (AJP), 2024)
Background and Objectives: Despite the available treatment options, people’s attitudes toward health changesignificantly. Evaluation of health status, and factors associated with health behaviors among adults in SaudiArabia. Materials and Methods: A cross-sectional web-based study was conducted in early, 2021 using avalid, self-administered online questionnaire, the data was analyzed using Statistical Package for Social Scienceversion 26. Results: Among the respondents a greater proportion of them were males 68.8% (n = 574), slightlymore than half 54.6% (n = 456) were consulted physicians, while 19.4% of them (n = 192) visited pharmacistsfor seeking health care, 16.4% (n = 137) used herbal or alternative medicine. A greater percentage of womenseek physicians (56.9%) in comparison to men (53.5%), while more men prefer to consult pharmacists (20%)in comparison to females (18.1%), also women used more herbal medicine for seeking treatment in comparisonto men. The health-seeking behavior is significantly associated with being a female gender (P = 0.0001),nationality of the participant (P = 0.0001, employment (P = 0.0001), and age of the individual (P = 0.0001).Conclusion: Increasing public understanding of the rational choice of seeking health care is a critical issue inmaintaining an individual’s health.